PENERAPAN METODE VIKOR DALAM SELEKSI PEMBERIAN REWARD PADA RESELLER CAN BEAUTY JOMBANG BERBASIS WEBSITE - Fajriyatus Sa’adah , Thulu’ul; Lazulfa , Indana; Andriani , Anita (Inovate, 2024)
Can Beauty is one of the businesses engaged in beauty in skin care. The provision of rewards to resellers is still seen from the success of sales achievement targets and there has been no assessment based on other supporting criteria. In addition, the selection process has not used a computerized system or by being directly selected by the Owner. From these problems, a decision support system is needed to solve the problem. The VIKOR method was chosen for its ability to classify and compromise existing alternatives. Therefore, this method is considered very effective when choosing in the selection of rewards to resellers. The VIKOR method is a simple rating method and can be used to choose from several criteria to get accurate results. By applying the VIKOR method, it is expected to be able to produce more accurate and objective output in the selection process of giving rewards to Can Beauty Jombang resellers. The calculation procedure for the VIKOR method in this system is based on predetermined standards, among others, the number of packages every 6 months, the type of transaction payment, the attitude of the reseller and the length of subscription. As well as weights for each criterion and obtained ranking results and taken the top 25 ranks. By using the VIKOR method, Can Beauty Jombang Distributors can determine which resellers are entitled to receive rewards. Keywords: Decision Support System, VIKOR, Reseller Reward